Special Issue on Deep Learning for Electroencephalography (EEG) Data Analysis - Roberto Prevete; Francesco Isgrò; Francesco Donnarumma (Applied Sciences, 2023)
Brain–computer interfaces (BCI) have emerged as a groundbreaking and transformative technology enabling communication between humans and computers through neural systems, primarily electroencephalography (EEG) [...]